Test and simulation the failure characteristics of twin tube shock absorber. (1st May 2019) - Guan, Dong; Jing, Xingjian; Shen, Hui; Jing, Li; Gong, Junjie
Graphical abstract: Highlights: The dynamic performance of twin tube shock absorber is tested. The failure characteristics are presented and analyzed. Virtual prototype is utilized to simulate and analyze the failure details. Abstract: Shock absorber is widely utilized in different engineering fields, such as automotive engineering, civil engineering and aerospace engineering, etc. In this paper, the dynamic performance of a twin-tube shock absorber is investigated by experiment and simulation. Force-velocity and Force-displacement curves are tested; results indicate damping force decreases abruptly at the end of compression stroke, when piston speed is between 0.31 and 0.75 m/s. Besides, damping force may also decrease at the end of rebound stroke when velocity continues increase. Furthermore, the virtual prototyping technology is proposed to further investigate dynamic properties of shock absorber. Effects of frequencies and vibration amplitudes on dynamics of shock absorber are comprehensively investigated. Dynamic stiffness and damping coefficients are investigated under multiply conditions. These results show the virtual prototype is an effective approach to characterize the dynamic performance of shock absorber; which can be further optimized under multiple conditions by such simulation. Design charts are also presented, to decide the operation domain of shock absorber.